Associations between cortical thickness, structural connectivity and severity of dimensional bulimia nervosa symptomatology. (30th January 2018) - Westwater, Margaret L.; Seidlitz, Jakob; Diederen, Kelly M.J.; Fischer, Sarah; Thompson, James C.
Abstract: Bulimia nervosa (BN) is a psychiatric illness defined by preoccupation with body image (cognitive 'symptoms'), binge eating and compensatory behaviors. Although diagnosed BN has been related to grey matter alterations, characterization of brain structure in women with a range of BN symptoms has not been made. This study examined whether cortical thickness (CT) values scaled with severity of BN cognitions in 33 women with variable BN pathology. We then assessed global structural connectivity (SC) of CT to determine if individual differences in global SC relate to BN symptom severity. We used the Eating Disorder Examination Questionnaire (EDE-Q) as a continuous measure of BN symptom severity. EDE-Q score was negatively related to global CT and local CT in the left middle frontal gyrus, right superior frontal gyrus and bilateral orbitofrontal cortex (OFC) and temporoparietal regions. Moreover, cortical thinning was most pronounced in regions with high global connectivity. Finally, individual contributions to global SC at the group level related to EDE-Q score, where increased EDE-Q score correlated with reduced connectivity of the left OFC and middle temporal cortex and increased connectivity of the right superior parietal lobule. Findings represent the first evidence of cortical thinning that relates to cognitive BN symptoms. Highlights: Bulimia nervosa (BN) symptoms related to cortical thinning in women with variable pathology. Cortical thinning was found in regions with high global structural connectivity. Individual contributions to structural connectivity related to BN symptom severity. Dimensional approaches to psychiatry may capture meaningful variance in neurobiology.